2011
DOI: 10.1007/s10681-011-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

Penalized regression techniques for modeling relationships between metabolites and tomato taste attributes

Abstract: The search for models which link tomato taste attributes to their metabolic profiling, is a main challenge within the breeding programs that aim to enhance tomato flavor. In this paper, we compared such models calculated by the traditional statistical approach, stepwise regression, with models obtained by the new generation of regression techniques, known as penalized regression or regularization methods. In addition, for penalized regression, different scenarios and various model selection criteria were discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…To assess chemical, sensorial and genetic diversity in cultivated tomato, a diversity panel (DP) of 94 cultivars was established by asking several leading breeding companies for cultivars of different genetic backgrounds and diverse fruit flavor characteristics. A comprehensive analysis of volatile compounds in fruits of this collection was performed and has been reported previously (Tikunov et al ., 2005; Ursem et al ., 2008; Menéndez et al ., 2012). To study the association between the genetic, chemical and sensorial variation further, a half diallel was developed by crossing the parents of four cultivars representative of the variation across the panel.…”
Section: Resultsmentioning
confidence: 99%
“…To assess chemical, sensorial and genetic diversity in cultivated tomato, a diversity panel (DP) of 94 cultivars was established by asking several leading breeding companies for cultivars of different genetic backgrounds and diverse fruit flavor characteristics. A comprehensive analysis of volatile compounds in fruits of this collection was performed and has been reported previously (Tikunov et al ., 2005; Ursem et al ., 2008; Menéndez et al ., 2012). To study the association between the genetic, chemical and sensorial variation further, a half diallel was developed by crossing the parents of four cultivars representative of the variation across the panel.…”
Section: Resultsmentioning
confidence: 99%
“…In order to find a candidate GT, an untargeted gene expression analysis using next-generation transcript sequencing called digital gene expression (DGE) was performed. Two groups, consisting of 25 'smoky' and 25 'nonsmoky' cultivars, were selected from a set of commercial cultivars characterized previously (Tikunov et al, 2005(Tikunov et al, , 2010Menéndez et al, 2012). Fruit material of each of the groups was pooled at two ripening stages: mature green (MG) and turning (T).…”
Section: Expression Of a Candidate Glycosyltransferase Correlates Witmentioning
confidence: 99%
“…The marker scores corresponded perfectly with PhP-V release (see Supplemental Figure 5 online). In addition, we genotyped a diverse set of commercial tomato cultivars (F1 hybrids), which had previously been profiled for taste and aroma and for volatile and nonvolatile metabolites (Tikunov et al, 2005(Tikunov et al, , 2010Menéndez et al, 2012). The two markers revealed 100% cosegregation with the different types of PhP-V glycoconjugates and the resulting difference in the release of the corresponding volatiles (see Supplemental Figure 6 online).…”
Section: Nsgt1-based Genetic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of regression, Kiers and Smilde [9] did a comparison of various multiple regression methods on simulated data with collinear variables, but their study was mainly focused on prediction and comparison of the regression coefficients when predictor variables are collinear. Menendez et al [23] reported comparison of stepwise linear regression, LASSO, EN and RR, but did not cover other penalization methods, such as SPLS, PLS, PCR, RF and SVM. We compare these methods (RR, EN, LASSO, SPLS, RF, SVM, PLS, PCR), in terms of mean square error of prediction, goodness of fit, variable selection and the ranking of the variables.…”
Section: Introductionmentioning
confidence: 99%